Preparação e caracterização de novos híbridos orgânicos-inorgânicos baseados em carboximetilcelulose/polifosfato de sódio dopados com 'Eu'Cl IND.3 - Reis, Felipe Costa Claro [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Organic- inorganic hybrid (HOI) are materials prepared with the combination of inorganic and organic components. The properties of a hybrid material are unique, not being the sum of each individual component added. This occurs because there is a synergism that depends of the chemical nature of organic and inorganic components, of the size and morphology of their domains. The sodium carboxymethylcellulose (CMC) it's an anionic polymer obtained of the cellulose, very soluble in water in which forms both solutions themselves and gels. The sodium polyphosphate (NaPO3)n, known commercially as Graham Salt is the only polyphosphate soluble in water, and it's the polyphosphate with the longest chain. At the present work it was prepared and characterized new phosphate organic- inorganic hybrids films of carboxymethylcellulose / sodium phosphate and luminescent films of CMC/NaPO3 doped with europium chloride (EuCl3). The films where prepared in several proportions. At first, it was set the amount of water to be used and the amount of carboxymethylcellulose, changing the concentrations of sodium polyphosphate and europium chloride. After pre-establishing concentrations, for each film, the components were submitted to constant agitation and subsequent drying. The inorganic-organic hybrid films were characterized by, TG, DR-X, DMA, FT-IR, UV-Vis-NIR, RMN 31P e 13C and at last, a study of luminescence was made. The hybrid films obtained are transparent and macroscopically homogeneous, however, the MET measures showed the formation of micro-islands of polyphosphate along the material, this fact indicates a bigger fragmentation of the films and this is verified by DMA analysis which shows a smaller resistance of the film with the increase of the concentration of phosphate. Both spectrum FT-IR and RMN analysis of the films, don't show the formation of new bands of their precursors, CMC e NaPO3,....
Keywords: Química inorgânica